Financial Profitability And Resource Productivity Analysis Of Garden Pea (Pisum Sativum L.) Production In Dhankuta, Nepal - Gahatraj, S; Subedi, R (SAARC Journal of Agriculture, 2020)
Garden pea is one of the economically and nutritionally most important winter vegetable crops in Nepal. Garden pea production is an emerging farm enterprise of Nepalese farmers of Eastern hill and mountain. The study was conducted to determine profitability, to investigate whether factors of production are being used in economic way, and to find out extension strategies for increasing income of farmers in Dhankuta district of Eastern Nepal. A total of 120 garden pea producing farmers, (60 from Chhathar-Jorpati Rural Municipality and 60 from Mahalaxmi Municipality of Dhankuta), were randomly selected and interviewed using semistructured interview schedule. Descriptive statistics and Cobb-Douglas production function were used to analyze the collected data. The benefit cost ratio (3.54) indicates that the garden pea production in study site was profitable with productivity of 6.59 Mt ha-1 per hectare. The production function revealed that cost on seed and labor have statistically significant effect on gross returns. In contrast, the effect of cost cost on plant nutrients and pesticides were not statistically significant. The sum of regression coefficients was 1.04 which indicates that production function exhibited an increasing return to scale. Thus, extension strategies should be primarily focused on introducing high yielding varieties, use of high quality seeds, providing trainings on improved farming practices, increasing value addition practices and strengthening market infrastructures. SAARC J. Agri., 17(2): 165-172 (2019)